Empowering medical students: Peer-Led OSCE reduces anxiety and may enhance test performance - Leonardo Mateus de Lima; Maria Helena Favarato; Iolanda Fátima Lopes Calvo Tibério (PLoS ONE, 2026)
Background The Objective Structured Clinical Examination (OSCE) is a widely used assessment method often associated with high levels of student anxiety and significant logistical demands, including time and professional resources. This study evaluated the impact of a peer-led mock OSCE intervention—wherein students conceptualized and administered the mock assessment—on anxiety levels and subsequent performance in summative OSCE. Methods Intervention: At the end of 2023, 28 third-year medical students taking the summative OSCE for the first time were randomized to participate in a peer-led mock OSCE, taking on roles as station designers, examiners, and examinees. An additional 39 students formed the control group, who did not participate in the intervention. Endpoints: Primary endpoint was state anxiety levels assessed with the State-Trait Anxiety Inventory (STAI); summative OSCE performance scores were a secondary endpoint. Results Students in the mock OSCE group demonstrated significantly lower state anxiety levels (54.80 ± 13.40) than the control group (63.56 ± 12.20, p = 0.009, Cohen's d = 0.692, mean difference = 8.79 points, 95% CI [2.25, 15.3]). Summative OSCE scores were numerically higher in the intervention group (8.60 ± 0.63) compared to control (8.30 ± 0.85, p = 0.055, r = 0.271, 95% CI [−0.000019, 0.600]), showing a favorable directional trend. Conclusion Participation in a peer-led mock OSCE significantly reduced state anxiety levels and may improve summative OSCE scores. This intervention may represent a valuable strategy to enhance both academic outcomes and student well-being in high-stakes medical assessments.